وظائف الإضمار الدلالية و التداولية عند النحاة - زبيدي, عتيق العربي, محمد الصالح حسين (University of El-oued, 2021)
ملخص الدراسة: الإضمار ظاهرة لغوية ، و هي من الدعائم الأساسية التي يقوم عليها النحو العربي. متأصلة في التراث العربي نظرا لميل العربية إلى الاختصار باستعمال الضمائر، التي تقوم مقام الأسماء الظاهرة. و للإضمار وظائف دلالية و تداولية تتعلق بالدلالات الصوتية و التركيبية للضمائر. و هو نوعان: إضمار بسيط ، و إضمار معقد حسب العمليات التي تتعلق بتحويل الاسم الظاهر إلى ضمير ، من خلال الصور المختلفة للمضمرات كإضمار الفاعل للفعل المبني للمعلوم و الفعل المبني للمجهول، و إضمار فاعل المصدر و مفعوله. و للإضمار وظائف دلالية تستند إلى البنيات اللغوية و وظائف تداولية ترتكز على مقامات الكلام و سياقاته . نلمح تلك الوظائف و الأغراض في النصوص القرآنية و الأحاديث النبوية و التراث العربي الشعري و النثري. و لا يقتصر دور الضمائر على تحقيق الترابط النصي فحسب بل له دور في تفسير معاني السياقات لمنح المتلقي أريحية في التفكير الإيجابي بأبهى صورة من جمال التعبير و سلامة التركيب، و وضوح المعنى. Study summary: Adhar is a linguistic phenomenon, and it is one of the mainstays of Arabic grammar. It is rooted in the Arab heritage due to the Arabic tendency to abbreviate the use of pronouns, which take the place of apparent nouns. Pronouns have semantic and pragmatic functions related to the phonetic and structural connotations of pronouns. It is of two types: simple pronoun, and complex pronoun according to the processes related to the transformation of the apparent noun into a pronoun, through the different forms of the pronouns, such as the subject pronoun of the active verb and the passive verb, and the infinitive and its object. It has semantic functions based on linguistic structures, and deliberative functions based on speech positions and contexts. We glimpse these functions and purposes in the Qur’anic texts, the hadiths of the Prophet, and the Arab heritage in poetry and prose. The role of pronouns is not limited to achieving textual coherence only, but also has a role in interpreting the meanings of contexts to give the recipient comfort in positive thinking in the best form of beauty of expression, integrity of structure, and clarity of meaning.
Keywords: الاضمار وظائف الاضمار